PELATIHAN METODE BERCERITA UNTUK MENINGKATKAN KEMAMPUAN BERBICARA ANAK - Hartani, Dwi; Purwantini, Lucky; Hanoum, Magdalena (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2023)
Hampered speaking skills will make it difficult for children to communicate with others. The child's inability to retell the content of the story that has been heard and the child has not been able to answer the question of the content of the story, this is due to the limitations of the learning in school and the absence of opportunities for the child to retell. This study aims to improve the speech ability of children aged 5-6 year. The treatment given is training using the method of telling stories with the medium of finger puppets. The research was conducted using the Quasi Experiment One group pretestpostest design approach. The research subjects of Cendikia Islamic School Kindergarten students aged 5-6 years were 14 children. Data collection was carried out using observation techniques, interviews and documentation. Data analysis of the results of the study using Paired Sample T-Test. The results of the analysis showed that there was a significant increase in speech skills in children after being given treatment. There was a difference in children's speaking ability before treatment of 30.14 and after treatment of 49.90, or children's speech ability increased by 19.76 (37%)